Analisis Gaya Kepemimpinan Kepala Desa dalam Menggerakkan Partisipasi Masyarakat (Studi Pengelolaan Dana Desa di Desa Banyurojo Kecamatan Mertoyudan Kabupaten Magelang) - Adinda Shauqina Ramadhani; Didik Gunawan Suharto (Universitas Sebelas Maret, 2022)
Community participation of the village funds management in Banyurojo village is inseparable from the leadership attitude of the Banyurojo Village head. The village head also involves the community in determining priorities for the use of village funds. The village head also provides opportunities for the community to be involved in the implementation of village development activities. To increasing community participation, of course each village head has a different leadership style. Therefore, this study aims to analyze how the village head’s leadership style in mobilizing community participation of the village fund management in Banyurojo Village, Mertoyudan District, Magelang Regency. This research is a qualitative descriptive research. Data was collected through interviews, observation, and documentation. Then analyzed using an interactive data analysis model according to Miles and Huberman. The results showed that in mobilizing community participation in the decision-making, benefit-taking, and evaluation stages of participation, the village head applied several leadership styles and the most dominant were democratic, charismatic and paternalistic leadership styles were also applied by the village head although not dominant. Then, in mobilizing community participation at the stage of implementing activities, the village head applies several leadership styles and the most dominant is democratic. In addition, the village head of Banyurojo also applies a charismatic, paternalistic, and laissez-faire (free control) leadership style, although it is not dominant.